Sosiologi Spiritualitas & Kesalehan Sosial - Romadhon, Sukron (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2020)
Spirituality and a new religious awakening, are seen by religious elites as a stage of religious directness in carrying out religious traditions and rituals. New civilizations can instead be a threat to conventional religious traditions and rituals. Without the willingness of religious elites to criticize and re-interpret conventional ritual traditions and patterns, the functions of the world's major religions could fade. The world's major religions are increasingly alienated from the objective world and awareness of the lives of the people and their people. It seems that there will be a new form of religion or a new religion that is completely different from the tradition of religious rituals that have been carried out by the major religions of the world. While the religious elite is still attached to classical religious interpretations. But on the other hand, the emergence of modern society, encouraging the argument of secularization is part of modernization. The values underlying socio-political and economic relations also appear to be beginning to enter an irregular stage, when viewed conventionally, the spiritulitas of global civilization, rather than lies in the format of values, traditional systems and structures or modern rationality. New civilizations in social systems and Science and Technology (SCIENCE AND TECHNOLOGY) began to be directed at a more intuitive spirituality stage. Then came the act of social piety that proved impartiality over the duafa wal mustad'afin, workers and the poor who were oppressed by the economic system. The emergence of the term left theology only wants to explain about righteousness and belief based on the ability to perform acts of liberation of the proletariat. This action is not only done after the reality of the proletariat appears, but creates a social and economic system that has impartiality towards the proletariat.